Using DSSAT-CENTURY Model to Simulate Soil Organic Carbon Dynamics Under a Low-Input Maize Cropping System - Musinguzi, Patrick; Ebanyat, Peter; Tenywa, John Stephen; Mwanjalolo, Majaliwa; Basamba, Twaha Ali; Tenywa, Moses M; Porter, Cheryl (My University, 2014)
Decline in Soil Organic Carbon (SOC) below the critical levels is one of the major indicators of soil fertility depletion in Sub-Saharan Africa (SSA), with the main causes being poor management practices coupled with low input use. Measures for monitoring long-term impacts of management on SOC dynamics and its restoration can be critical in enhancing sustainable soil productivity. Crop models have proved to be good tools for understanding the influence of management options on soil and crop productivity. The DSSAT-Century model was applied to simulate the influence of management practices on SOC dynamics. Using long-term datasets from Kabete, Kenya (1976-1996 maize-bean) and Kiboga-Uganda (1980-2010 maize), model calibration and evaluation showed a good fit between simulated and observed values of SOC. On simulating continuous tillage with no fertilization for the 1980-2010 antecedent period and 2010-2060 extrapolated period, the model showed high rates of SOC decline in the newly cultivated soil as compared to a degraded soil. The simulated rate of decline is 2129 kg ha-1 yr-1 for newly cultivated soil and 849 kg ha-1 yr-1 for the continuously cultivated soils. The model was sensitive to initial partitioning of SOC pools, with SOC in previously uncultivated soils declining at a higher rate than that in the cultivated ones. The model confirmed that use of continuous tillage is a major threat to SOC building and soil fertility restoration in the tropics. Adopting conservation agriculture is critical for future generations. Overall, the DSSAT CENTURY model is a potential tool for predicting SOC dynamics in low-input farming systems.
Keywords: simulation, dynamics, long-term, carbon pools, tropical soil